PERANCANGAN APLIKASI HOME SERVICE MENGGUNAKAN PROGRESSIVE WEB APPLICATION - Atikah Atikah; Asrul Huda (Universitas Negeri Padang, 2019)
The rapid development of technology is widely used in various fields, one of which is the field of cleaning services. In the past, women worked on cleaning at home while men went to work out of the house. Nowadays, the changing patterns of life of the people demand that women and men spend their time going out of the house to work. Activities in homes that are getting denser but unchanged services result in imbalance, so people need to do cleaning at home. The solution to these problems is to make a home service application that provides home cleaning services. In making the application used to the yii2 framework, progressive web application and the waterfall method. This home service application provides internal and outdoor cleaning services that can be ordered wherever and whenever.Keywords: Home service, progressive web application, waterfall